In vivo Evaluation of Two Thiazolidin-4-one Derivatives in High Sucrose Diet Fed Pre-diabetic Mice and Their Modulatory Effect on AMPK, Akt and p38 MAP Kinase in L6 Cells - Mudgal, Jayesh; Shetty, Priya; Reddy, Neetinkumar D.; Akhila, H. S.; Gourishetti, Karthik; Mathew, Geetha; Nayak, Pawan G.; Kumar, Nitesh; Kishore, Anoop; Kutty, Nampurath G.; Nandakumar, Krishnadas; Shenoy, Rekha R.; et al. (Frontiers in Pharmacology, 2016)
We had previously demonstrated the anti-diabetic potential and pancreatic protection of two thiazolidin-4-one derivatives containing nicotinamide moiety (NAT-1 and NAT-2) in STZ-induced diabetic mice. However, due to the limitations of the STZ model, we decided to undertake a detailed evaluation of anti-diabetic potential of the molecules on a high sucrose diet (HSD) fed diabetic mouse model. Further, in vitro mechanistic studies on the phosphorylation of AMPK, Akt and p38 MAP kinase in L6 myotubes and anti-inflammatory studies in RAW264.7 mouse monocyte macrophage cells were performed. 15 months of HSD induced fasting hyperglycaemia and impaired glucose tolerance in mice. Treatment with NAT-1 and NAT-2 (100 mg/kg) for 45 days significantly improved the glucose tolerance and lowered fasting blood glucose levels compared to untreated control. An improvement in the elevated triglycerides and total cholesterol levels, and favourable rise in HDL cholesterol were also observed with test drug treatment. Also, no major changes were observed in the liver (albumin, AST and ALT) and kidney (creatinine and urea) parameters. This was further confirmed in their respective histology profiles which revealed no gross morphological changes. In L6 cells, significant phosphorylation of Akt and p38 MAP kinase proteins were observed with 100 μM of NAT-1 and NAT-2 with no significant changes in phosphorylation of AMPK. The molecules failed to exhibit anti-inflammatory activity as observed by their effect on the generation of ROS and nitrite, and nuclear levels of NF-B in LPS-stimulated RAW264.7 cells. In summary, the molecules activated Akt and p38 MAP kinase which could have partly contributed to their anti-hyperglycaemic and hypolipidaemic activities in vivo.